Comparative transcriptome analysis reveals the key role of photosynthetic traits in the formation of differences in photothermal sensitivity in tobacco - Yanfeng Zheng; Qiwei Yu; Anbin Lu; Xiue Chen; Kai Yang; Jingyao Zhang; Ying Huang; Renxiang Liu (BMC Genomics)
Abstract Background The photothermal sensitivity of tobacco refers to how tobacco plants respond to variations in the photothermal conditions of their growth environment. The degree of this sensitivity is crucial for determining the optimal planting regions for specific varieties, as well as for improving the quality and yield of tobacco leaves. However, the precise mechanisms underlying the development of photothermal sensitivity in tobacco remain unclear. Results In this study, two tobacco varieties with significant differences in sensitivity, previously selected using a photothermal sensitivity model, were chosen as materials. Two experimental sites with considerable differences in photothermal conditions were selected for planting. The aim was to comparatively analyze the changes in agronomic traits, biomass, and physiological indices of the varieties under different experimental conditions, as well as to conduct transcriptome analyses. The transcriptome results revealed significant enrichment of differentially expressed genes (DEGs) related to photosynthesis, plant hormone signal transduction, and flavonoid biosynthesis pathways. In the photosynthesis and plant hormone signaling pathways, genes such as Lhcb, aldo, AUX/IAA, and SAUR were significantly upregulated. This upregulation promoted photosynthetic efficiency by enhancing the process of photosynthesis. However, this promotion also led to the increased production of harmful substances such as hydrogen peroxide and superoxide radicals, which can damage cellular structure and function. In the flavonoid biosynthesis pathway, genes such as FLS, CHI, and PAL were significantly upregulated, which enhanced the plant’s antioxidant capacity. This effectively mitigated the harmful effects of oxidative stress, helping to maintain normal photosynthetic function. Conclusion The findings of this study suggest that the photosynthetic capacity of tobacco plants is enhanced through the coordinated regulation of the photosynthesis, plant hormone signaling, and flavonoid biosynthesis pathways. This enhancement plays a pivotal role in modulating the plants’ photothermal adaptability, ultimately contributing to variations in their photothermal sensitivity.